Hedging Effectiveness Analysis of High Market Cap Indian Stocks using OLS and GARCH Hedge Ratios (Global Journal of Management and Business Research, 2017)
Abstract not found
Keywords: hedging; high market capitalization; index futures; OLS; GARC